Robust mechanical properties of Ag2Se1–xTex thermoelectric materials - Chen Heyang; Ren Shenghong; Feng Hengyang; Wei Tian-Ran; Fu Ling; Pan Zhenyu; Zhao Kunpeng; Li Xiuyan; Shi Xun (National Science Open)
High mechanical robustness is essential to the material’s processibility for the applications in flexible and miniaturized electronics. As state-of-the-art room-temperature thermoelectric materials, Ag2Se1–xTex alloys exhibit superior thermoelectric transport properties but their mechanical properties remain largely unexplored. Herein, we systematically investigate the mechanical and thermoelectric properties of a series of Ag2Se1–xTex materials. Among them, Ag2Se0.9Te0.1 shows robust mechanical properties including a large compression strain of (26.7 ± 4.5)%, a high compression strength of (279.2 ± 49) MPa, and an excellent fracture toughness of (4.5 ± 0.6) MPa m1/2. These robust mechanical properties are ascribed to the dense dislocations as well as possible sub-grain rotations. Combined with the excellent thermoelectric figure of merit, zT of 0.78 at 300 K and 1.1 at 380 K, the Ag2Se1–xTex alloys are promising candidates for robust and efficient thermoelectric applications near room temperature.